Inibição dos principais efeitos tóxicos causados por venenos animais pelo extrato vegetal de Casearia sylvestris (Flacourtiaceae) - Borges, Márcia Helena (1998)
Snake venoms are constituted by complex mixtures of proteases, hemorrhagic factors and phospholipases that are responsible for the main effects of the envenomations such as: myotoxicity, hemorrhage, disturbs of blood coagulation and edema. Many plants have been used in popular medicine for the treatment of snakebite, but its use has generally been attributed to the superstition and there are few scientific knowledge related to the characteristics presented by these plants. The purpose of this study was to verify the inhibition of the Bothrops jararacussu, Bothrops neuwiedi pauloensis and Apis mellifera venoms main effects by Casearia sylvestris (Flacourtiaceae) extract, a typical plant from Brazilian Savannah. Initially, an acjueous extract was prepared from the leaves and the stem of this plant and this extract was incubated with the crude venom sample by one hour before the test. We realized some activities as Phospholipase A2, blood coagulation, fibrinogenolytic, hemorrhagic, myotoxic, edema and toxicity. For Phospholipase A2 activity the results indicate a high percentage of inhibition for all the venoms, where the statistical analysis revealed that these extract inhibited significantly and that the both extracts (stem and leaves) are equally efficient. In the coagulation activity the results were statistically analyzed by the test T and showed significant differences only to B.jararacussu venom incubated with Casearia sylvestris leaves (inhibition of 38/o), while for the other samples, no significant neutralization was recorded. When we tested the inhibition of the fibrinogenolytic activity, we found that the extract (leaves or stem) offered little or no protection for the fibrinogen ct chain. The inactivation of the hemorrhagic activity was determined by intradermic injections in mice. The hemorrhagic activity presented great inhibition for the stem and leaves extract, suggesting the efficiency of this extract for this activity. For myotoxic activity, the histological observations show fibers in perfect State for the samples incubated with the extract when compared to the those that contained only venom and they indicate the presence of the components able to neutralize the toxic effects. In the edema activity was verified that the edema was not inhibited by the extract of the leaves of Casearia sylvestris, but the edema produced by the sample incubated with the extract was lightly smaller than that provoked by the venom in the extract absence. Finally, for toxicity test, the Casearia sylvestris extract provoked an increase in the lifetime of the animais that received intraperitonials injections of 2DL50 (lethal dose) of Bothrops jararacussu and Bothrops neuwiedi pauloensis venoms when these were incubated with the stem or leaves extract. Despite all the animais died along the experiment, the lifetime average was prolonged and it showed significant results for Bothrops jararacussu venom. For all the activities, negative Controls were accomplished, using only the extracts and we can conclude that these extracts don't induce to any activity. In agreement with the results above, we verified that Casearia sylvestris (Flacourtiaceae) extract can neutralize animais venoms. The high inhibition percentages for the hemorrhagic, phospholipase A2 and myotoxic activities, indicate the presence of components that could present great therapeutic value for treatment of animal envenomations and perhaps to for another clinicai disorders.